Zero-dimensional transient model of large-scale cooling ponds using well-mixed approach. (April 2018) - Ramadan, Ahmed; Hasan, Reaz; Penlington, Roger
Highlights: An analytical model of large-scale cooling pond is developed based on well-mixed approach. The model is validated for typical ponds size and for large-scale pond for normal operational conditions. The model is able to predict the thermal behaviour and the water level of the cooling pond. The model can provide a very quick answer to what if scenarios. Pond temperature is sensitive to the outside environment temperature. Abstract: Nowadays, nuclear power plants around the world produce vast amounts of spent fuel. After discharge, it requires adequate cooling to prevent radioactive materials being released into the environment. One of the systems available to provide such cooling is the spent fuel cooling pond. The recent incident at Fukushima, Japan shows that these cooling ponds are associated with safety concerns and scientific studies are required to analyse their thermal performance. However, the modelling of spent fuel cooling ponds can be very challenging. Due to their large size and the complex phenomena of heat and mass transfer involved in such systems. In the present study, we have developed a zero-dimensional (Z-D) model based on the well-mixed approach for a large-scale cooling pond. This model requires low computational time compared with other methods such as computational fluid dynamics (CFD) but gives reasonable results are key performance data. This Z-D model takes into account the heat transfer processes taking place within the water body and the volume of humid air above its surface as well as the ventilation system. The methodology of the Z-D model was validated against data collected from existing cooling ponds. A number of studies are conducted considering normal operating conditions as well as in a loss of cooling scenario. Moreover, a discussion of the implications of the assumption to neglect heat loss from the water surface in the context of large-scale ponds is also presented. Also, a sensitivity study is performed to examine the effect of weather conditions on pond performance.